PELATIHAN PEMASARAN DARING BAGI KELOMPOK USAHA PENGOLAHAN IKAN MINA SEKAR DI DESA TAMBAK OSO - Muchammad Tamyiz; Waluyo Prasetyo; Fuad Achmadi (Journal of Science and Social Development, 2019)
The availability of coastal natural resources provides a great opportunity for residents of Tambak Oso village. This condition makes the residents of Tambak Oso village create a business group "Mina Sekar" which is engaged in processing foodstuffs derived from fish. Based on the analysis of the situation and problems that occur in the fish processing business group in Tambak Oso Village, the problemsolving framework is to use the training and mentoring approach. Therefore, training related to online marketing for fish processing business groups in Tambak Oso Village. The conclusion of this activity is that all members of the Mina Sekar fish processing business group in Tambak Oso Village are of productive age, 95% of respondents can understand online marketing material, only 5% or 1 respondent cannot understand online marketing material, and 60% of respondents have diversify processed fish products.